Managerial Talent and Corporate Social Responsibility (CSR): How Do Talented Managers View Corporate Social Responsibility? - Chatjuthamard, Pattanaporn; Jiraporn, Pornsit; Tong, Shenghui; Singh, Manohar (International Review of Finance, 2016)
Motivated by the ongoing debate on the costs and benefits of corporate social responsibility (CSR), we explore how talented managers view CSR investments. Based on nearly 20,000 observations across 17 years, our evidence reveals a nonmonotonic effect of managerial talent on CSR. Exploiting a novel measure of managerial ability, we find that talented managers view CSR investments favorably. However, only those with especially strong talent are in favor of CSR investments. For executives ranked above the 75th percentile in terms of managerial talent, an increase in managerial ability leads to more CSR investments, suggesting that these strongly talented managers perceive CSR as enhancing firm performance. In contrast, for those with weaker talent, CSR investments are negatively associated with managerial ability, implying that these weakly talented managers view CSR as a wasteful deployment of resources. Further evidence shows that our conclusion is unlikely confounded by endogeneity.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/irfi.12067
Keywords: G30; G32; M14; dept.mrk